Rancang Bangun Aplikasi Edukasi Reproduksi Manusia Pada Pelajar SMPN 187 Jakarta Berbasis Android - Djunaedi, Bagas; Malabay; Yulhendri; Tjahjono, Budi (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The implementation of education at SMPN 187 Jakarta is often limited to the use of PPT and RPP, causing the material to become monotonous and less interesting for students. Reproduction education is also often not delivered comprehensively, resulting in less than optimal student understanding. To overcome this, an Android-based application was developed which aims to increase students’ understanding of reproductive health. This application provides educational material covering secondary and primary aspects as well as a test feature to measure student understanding, making learning more effective and interactive. This application uses Flutter as a multi-platformframework andDart as an open source programming languagewithOOPconcepts that are easy to understand. The application backend is managed with Laravel, functioning as BackendAPImanagement of themobile application.The prototypemethod is used in development, starting from collecting user needs to creating a design/prototype. The results of this research are as an educational application and learning support media for students at SMPN 187 Jakarta by making learning media flexible and efficient, with features for characters that help improve students’ and female students’ understanding of educational reproduction.